CORIOLIS VIBRATION GYROSCOPE WITH METAL CYLINDRICAL RESONATOR - Chikovani, V. V.; Yatsenko , Yu.A.; Kovalenko, V. A. (Problems of Informatization and Management, 2021)
The Coriolis Vibrating Gyroscope (CVG) is an angular velocity sensor with no rotating parts. This gyroscope, using a metal cylinder as a resonator, is comparable in size to many types of micromechanical gyroscopes (MMG) [1], intensively developed in Europe and the USA. At present, the quartz resonator KVG [2] has been recognized in the United States as the most reliable gyroscope with 4.5 million MTBF and accepted by Northrop Grumman for serial production.